Practices of personal adornment in Neolithic Greece - Ifantidis, Fotis, (Access archaeology., 2019)
The objective of this text is the reconsideration of the practices of personal adornment during the Neolithic period in Greece, through the assemblage, extensive bibliographic documentation, and critical evaluation of all the available data deriving from more than a hundred sites in the mainland and the Aegean islands.